Item Analysis for the Adapted Motivation Scale Using Rasch Model - Sar Ee Ng; Kee Jiar Yeo; Azlina bt Mohd Kosnin (Institute of Advanced Engineering and Science, 2018)
The aim of this study was to measure the validity and reliability of an adapted motivation scale used in second language learning. The Integrative and Instrumental motivation (IIM) was developed based on two orientations of motivation, which were integrative motivation and instrumental motivation. IIM was used to identify students’ level of motivation towards learning Chinese language as a second language (CLSL) in national school. The study presented empirical evidence of validity and reliability using the Rasch Model. Pilot study was conducted in a national school which has students enrolled for the CLSL class. There were 29 students in this pilot study. Data was analyzed using WINSTEPS version 3.72.3. The result showed the reliability of the motivation scale is 0.87 based on Cronbach’s alpha. The construct validity was determined by PT-measure correlation value (PMC) range from 0.71 to 0.86, infit and outfit MNSQ between 0.53 to 1.43 and ZSTD range from -1.1 to 1.2. In unidimensional measure, raw variance explained was at 66.4% with the unexplanined variance in the first factor was at 13.6%. Finally the fit statistics showed that person separation index, 2.79 was considered good and item separation index, 1.81was in acceptable range (Linacre,2012). Person and item reliability were at 0.89 and 0.77 respectively. The result indicated that the new instrument with 15 items-IIM after eliminated unfit items was a reliable and valid instrument to measure the motivation in learning CLSL in the context of national school.